Thyroid hormone treated astrocytes induce maturation of cerebral cortical neurons through modulation of proteoglycan levels - Dezonne, Romulo S.; Stipursky, Joice; Araujo, Ana Paula B.; Nones, Jader; Pavão, Mauro Sérgio G.; Porcionatto, Marimelia; Gomes, Flavia C. (Frontiers in Cellular Neuroscience, 2013)
Proper brain neuronal circuitry formation and synapse development is dependent on specific cues, either genetic or epigenetic, provided by the surrounding neural environment. Within these signals, thyroid hormones (T3 and T4) play crucial role in several steps of brain morphogenesis including proliferation of progenitor cells, neuronal differentiation, maturation, migration, and synapse formation. The lack of thyroid hormones during childhood is associated with several impair neuronal connections, cognitive deficits, and mental disorders. Many of the thyroid hormones effects are mediated by astrocytes, although the mechanisms underlying these events are still unknown. In this work, we investigated the effect of 3, 5, 3′-triiodothyronine-treated (T3-treated) astrocytes on cerebral cortex neuronal differentiation. Culture of neural progenitors from embryonic cerebral cortex mice onto T3-treated astrocyte monolayers yielded an increment in neuronal population, followed by enhancement of neuronal maturation, arborization and neurite outgrowth. In addition, real time PCR assays revealed an increase in the levels of the heparan sulfate proteoglycans, Glypican 1 (GPC-1) and Syndecans 3 e 4 (SDC-3 e SDC-4), followed by a decrease in the levels of the chondroitin sulfate proteoglycan, Versican. Disruption of glycosaminoglycan chains by chondroitinase AC or heparanase III completely abolished the effects of T3-treated astrocytes on neuronal morphogenesis. Our work provides evidence that astrocytes are key mediators of T3 actions on cerebral cortex neuronal development and identified potential molecules and pathways involved in neurite extension; which might eventually contribute to a better understanding of axonal regeneration, synapse formation, and neuronal circuitry recover.